The question of derivatives: promoting use and ensuring availability of non-proprietary plant genetic resources - Fowler, Cary; Engels, J.; Frison, Emile A.; International Plant Genetic Resources Institute (2003)
The interface between plant genetic resources that are in the public domain and intellectual property rights regimes is a dynamic one, characterized by tension and even controversy. It has been this way for many years. Society's interests lie in encouraging innovation with and use of plant genetic resources. In this respect the balance between the need to keep access to genetic resources unfettered so that anyone can use them and the need to allow innovators to claim certain property rights over their creations as a means of encouraging and rewarding such work is critically important. The centerpiece of this publication is an article - reprinted with permission from the Journal of World Intellectual Property - that focuses on the question, ”How much or how little must be done to germplasm accessed from the public domain before a grant of intellectual property right can be sought?” The article examines the practices of centres of the Consultative Group on International Agricultural Research (CGIAR) and seeks to help the reader work through and evaluate a range of different options for how rules regarding derivatives might be handled in the future. In addition, this publication brings together a number of key related documents: the agreements between the CGIAR centres and the Food and Agriculture Organization of the United Nations (FAO) placing plant germplasm held by the centres under the auspices of the FAO; the joint statements issued by FAO and CGIAR concerning these agreements; the two Material Transfer Agreements (MTAs) that the CGIAR Centres have used ; and the relevant sections of the International Treaty on Plant Genetic Resources for Food and Agriculture that will provide the legal context and framework for future rule systems dealing with the interface between germplasm and intellectual property rights regimes.